PENGUATAN KELEMBAGAAN KELOMPOK TANI PEMERHATI SUNGAI “NGUDI MULYO” DESA GEDONGREJO, GIRIWOYO, WONOGIRI - Robertus Sudaryanto; Sumani Sumani; Purwanto Purwanto; Supriyadi Supriyadi (Caraka Tani: Journal of Sustainable Agriculture, 2017)
LOCATION: was conducted at Ngulang, Gedongrejo, Giriwoyo, Wonogiri district. With the TITLE: the use of Syperus ratandus (rumput gelagah) and Vetivera zizanoides (akar wangi) fr river edge and riverbank reinforcement at Ngulang, Gedongrejo, Giriwoyo, Wonogiri district. PURPOSE: 1) to response the desire and requirement if surrounding society to protect and prevent he Bengawan Solo upper riverbank from sliding and flood threat; 2) socialization a model of soil and water conservation by cultivating Syperus ratandus and Vetivera zizanoides that supported by the society; 3)  to motivate the society for cultivate the Vetivera zizanoides, which both economical, conservation innovation and networking. METHOD: 1) field observation; 2) focus group discussion. RESULT: plot model conservation 700x20 m (left and right side of riverbank) and giving example akar wangi one lane all along the river (±700 m), 2) unionize a riverbank observers group. CONCLUSION: 1) the surrounding society of Ngulang are positively response to this activity; 2) the riverbank observer group of the surrounding society was formed, called as “Ngudi Mulyo”; 3) plot model conservation (±700 m); 4) when the river flood, akar wangi and gelagah actually can protect and prevent the riverbank. IMPLICATION: 1) institution strengthening, 2) development for the peasants that do not obtain the facilities at this program, 3) training of livestock waste and litter management, 4) market network strengthening.